Pola Mikroba dan Sensitivitasnya Terhadap Antibiotik pada Pasien dengan Infeksi Saluran Kemih di RSUD Prof. Dr. W.Z. Johannes, Kupang Periode Januari-Desember 2017 - Vivi Anggelia; Clarissa Oktavia; Heri Sutrisno; Hermi Indita (DiscoverSys Inc., 2020)
Background: Urinary tract infection (UTI) is a serious public health problem which involves infection of any parts of the urinary tract. In the past few years, treatment of UTI becomes very challenging due to increase emergence of antibiotics resistance in uro-pathogens. This study was performed to determine microbial patterns and its sensitivity to antibiotics.Methods: This was an observational descriptive study. The data were collected from 130 urine samples in RSUD Prof. Dr. W.Z. Johannes during period of January-December 2017. Patients were diagnosed UTI by using Vitek 2.Results: We obtained 130 samples of urine culture in RSUD. Prof. Dr. W. Z. Johannes during period of January-December 2017. From 130 samples of urine culture, 83 samples showed growth of bacteria and fungi (63,85%) whereas 47 samples showed no growth (36,15%). From 83 growth samples, we identified 20 types of bacteria which include 4 types of gram positive bacteria, 16 types of gram negative bacteria and 1 type of fungi. The most common causes of UTI were E. coli (22,89%), Candida albicans (10,84%), Klebsiella pneumoniae ss pneumoniae (9,64%) and Acinetobacter baumanii (6,02%). Meropenem, gentamycin and amikacin were still sensitive to uropathogen. The most common antibiotics which were resistance to bacteria were ampicillin and ceftriaxone.Conclusion: Escherichia coli is the most prevalence contribute to UTI in outpatient and inpatient. There were only three types of non-resistant antibiotic to uropathogens.Â Latar Belakang: Infeksi saluran kemih (ISK) merupakan salah satu masalah kesehatan serius. Beberapa tahun belakangan ini, pengobatan ISK menjadi tantangan tersendiri bagi para klinisi karena tingginya angka resistensi antibiotik. Penelitian ini bertujuan untuk mengetahui pola mikroba dan senstivitasnya terhadap antibiotik.Metode: Pada penelitian deskriptif observasional ini, didapatkan 130 sampel urin di RSUD Prof. Dr. W.Z. Johannes dari bulan Januari-Desember 2017 dimana pasien didiagnosis ISK melalui pemeriksaan dengan Vitek 2.Hasil: Sebanyak 130 sampel urin yang dikultur, 83 sampel menunjukan perkembangan bakteri dan jamur (63,85%) dimana 47 sampel menunjukan tidak adanya pertumbuhan (36,15%). Dari 83 sampel yang tumbuh, teridentifikasi sebanyak 20 tipe bakteri dimana 4 tipe merupakan gram-positif dan 16 tipe gram negatif serta 1 tipe jamur. Penyebab terbanyak ISK adalah E. coli (22,89%), Candida albicans (10,84%), Klebsiella pneumoniae ss pneumoniae (9,64%) dan Acinetobacter baumanii (6,02%). Dimana antibiotik jenis meropenem, gentamisin dan amikasin masih sensitif untuk uropatogen. Sedangkan ampisilin dan seftriakson adalah jenis antibiotik yang memiliki angka resistensi tertinggi.Kesimpulan: Escherichia coli adalah penyebab tersering ISK dan hanya ditemukan tiga jenis antibiotik yang masih sensitif untuk uropatogen.